Energy Economics Theory and Applications - Zweifel, Peter; Praktiknjo, Aaron; Erdmann, Georg; SpringerLink (Online service) ([Place of publication not identified] : SPRINGER, 2017)
This book provides an introduction to energy economics. It shows how to apply general economic theory as well as empirical and advanced econometric methods to explain the drivers of energy markets and their development. Readers learn about the specific properties of energy markets as well as the physical, technological, environmental, and geopolitical particularities of energy sources and products. The book covers all types of energy markets, ranging from liquid fuels, gaseous fuels, and solid fuels to electricity. It also addresses emission allowances, energy efficiency, and nuclear risks. The authors discuss the engineering properties of energy technologies including renewables, the economics of natural resources and environmental protection, market liberalization, and energy trade as well as the experience of the German energy transformation. This book will serve students as a textbook and practitioners as a reference for their understanding of energy markets and their development.
Preface -- Introduction -- Energy in Science and Engineering -- Investment and Profitability Calculation -- Bottom-Up Analysis of Energy Demand -- Top-Down Analysis of Energy Demand -- Energy Reserves and Sustainability -- External Costs -- Markets for Liquid Fuels -- Markets for Gaseous Fuels -- Markets for Solid Fuels and CO2 Emissions -- Uranium and Nuclear Energy -- Markets for Electricity -- Economics of Electrical Grids.
Includes bibliographical references and indexes.
Keywords: Energy policy; Energy and state; Environmental economics; Economic policy; Industrial organization; Energy Policy, Economics and Management; Environmental Economics; Economic Policy; Energy Policy, Economics and Management; Industrial Organization